PERIODONTAL RISKS AND COMPLICATIONS CORRELATED WITH ORTHODONTIC TREATMENT. A REVIEW - Ioana-Andreea Sioustis; Ionut Luchian; Alexandra-Maria Martu; Diana-Cristala N; Irina-Georgeta Sufaru; Liliana Pasarin; Bogdan Vasiliu; Sorina-Mihaela Solomon (Romanian Dental Association for Education, 2019)
Periodontal health may be used to evaluate the success of orthodontic treatment. Orthodontic treatment ensures proper alignment of the teeth and improves the occlusal and jaw relationship. This improves the quality of life, contributing to oral and general health. Orthodontic treatment has benefits, but also risks and complications. Oral hygiene instruction and periodontal therapy are also indicated for child and adolescent orthodontic patients. This review highlights three most important periodontal complications of the orthodontic treatment and it assesses the necessity of the periodical periodontal controls and treatments before, during and after the orthodontic treatment.